What are the effects of soil treatment procedures (sterilization by γ-irradiation and solvent-assisted spiking) on DDE bioaccumulation by earthworms? - Škulcová, Lucia; Scherr, Kerstin E; Hofman, Jakub; Bielská, Lucie (Environmental pollution (Barking, Essex, 2018)
Ionizing γ-irradiation and solvent-assisted spiking are frequently applied to eliminate microbial activity and to induce hydrophobic organic compounds (HOCs) into soil, respectively, when studying the accumulation of chemicals in terrestrial organisms. However, the side-effects that may arise from these treatments on soil-HOC interaction and, subsequently, the kinetics and extents of bioaccumulation are not thoroughly understood. To this end, the accumulation of 1,1-dichloro-2,2-bis(p-chlorophenyl)etylene (p,p'-DDE) by Eisenia andrei was studied in sterilized or unsterilized and freshly spiked (FS) or historically contaminated (HC) soils in parallel with an analysis of aliphatic and hydrophilic soil organic matter (SOM) moieties using mid-infrared diffuse reflectance spectroscopy (DRIFT-S). Irradiation did not impart significant changes on spectral SOM descriptors. In contrast, earthworm inhabitation increased the relative presence of aliphatic moieties to a greater extent than hydrophilic ones, reaching or exceeding pre-treatment levels. Overall, effects on SOM chemistry can be ranked as earthworms > spiking > irradiation. Corresponding changes at the bioaccumulation level were observed for the FS soil (i.e., a 27% reduction in bioaccumulation upon sterilization) but not for the HC soil. This implies that in contrast to the interactions between aged p,p'-DDE and sterilized HC soil, the interactions established between freshly added p,p'-DDE and sterilized FS soil were altered by γ-irradiation-induced secondary effects alone or in combination with earthworm inhabitation. Thus, although the soil treatment processes studied here should not drastically impact compound bioaccumulation, they should be considered in mechanistic studies where the qualitative and quantitative aspects of compound-soil (organic matter)-earthworm interactions are at the centre of attention.
Keywords: Organic Chemicals; záření gama; Sterilization; Animals; dichlordifenyldichlorethylen; Gamma Rays; DRIFT-S; Soil Pollutants; Oligochaeta; Solvents; sterilization; Soil organic matter; látky znečišťující půdu; znečištění životního prostředí; Dichlorodiphenyl Dichloroethylene; Eisenia andrei; Environmental Pollution; rozpouštědla; Bioaccumulation; sterilizace; organické látky; zvířata; Soil; půda; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions